Poverty Reduction Community And Social Development Projects (Csdp) In Yobe State, Nigeria - Suleiman, Kawuwa (2023)
Poverty is increasingly affecting development and wellbeing in Sub-Sahara Africa, Nigeria and Yobe State in particular. Many communities suffer from poverty due to inadequate access to basic infrastructure of health, education, water, and environmental projects. The Community and Social Development Project (CSDP) is a poverty reduction programme which provides micro infrastructure projects in Yobe state. Therefore, this study explores the effects of the CSDP infrastructure projects on wellbeing and poverty reduction. The study also finds out the community perception on CSDP poverty reduction strategies as well as stakeholders’ views on the challenges of poverty reduction programme in Yobe state. The study adopted a mixed-method approach to data collection. The method involved the use of techniques of both quantitative and qualitative methods of data collection. The study also adopted a multi-stage cluster sampling technique in which Yobe State was divided into the existing Senatorial Zones, States, LGAs and Communities. A total of 360 respondents were selected and served with questionnaires while Key Informant Interviews (KIIs) were conducted with three participants, one each from CSDP, Yobe State Ministry of Social Welfare, and CSOs. Moreover, twelve Focus Group Discussion (FGD) sessions were conducted with relevant stakeholders across the twelve communities selected for the study. The quantitative data was analysed using Statistical Package for Social Science (SPSS) and Smart Partial Least Square Structural Equation Modelling (SmartPLS) software and the qualitative data was analysed with thematic analysis of codes, categories and themes identification.